# Prove $\int_0^\infty \frac{\sin^4x}{x^4}dx = \frac{\pi}{3}$

I need to show that $$\int_0^\infty \frac{\sin^4x}{x^4}dx = \frac{\pi}{3}$$

I have already derived the result $\int_0^\infty \frac{\sin^2x}{x^2} = \frac{\pi}{2}$ using complex analysis, a result which I am supposed to start from. Using a change of variable $x \mapsto 2x$ :

$$\int_0^\infty \frac{\sin^2(2x)}{x^2}dx = \pi$$

Now using the identity $\sin^2(2x) = 4\sin^2x - 4\sin^4x$, we obtain

$$\int_0^\infty \frac{\sin^2x - \sin^4x}{x^2}dx = \frac{\pi}{4}$$ $$\frac{\pi}{2} - \int_0^\infty \frac{\sin^4x}{x^2}dx = \frac{\pi}{4}$$ $$\int_0^\infty \frac{\sin^4x}{x^2}dx = \frac{\pi}{4}$$

But I am now at a loss as to how to make $x^4$ appear at the denominator. Any ideas appreciated.

Important: I must start from $\int_0^\infty \frac{\sin^2x}{x^2}dx$, and use the change of variable and identity mentioned above

-
Check this technique. – Mhenni Benghorbal Mar 31 '14 at 22:34

You are likely expected to integrate by parts (twice) $$\begin{eqnarray} \int \frac{\sin^4(x)}{x^4} \mathrm{d}x &=& -\frac{1}{3} \frac{\sin^4(x)}{x^3} + \frac{4}{3} \int \frac{\cos(x) \sin^3(x) }{x^3} \mathrm{d} x \\ &=& -\frac{1}{3} \frac{\sin^4(x)}{x^3} -\frac{2 \cos(x) \sin^3(x)}{3 x^2} + \frac{2}{3} \int \frac{3 \cos^2(x) \sin^2(x) - \sin^4(x)}{x^2} \mathrm{d} x \\ &=& -\frac{1}{3} \frac{\sin^4(x)}{x^3} -\frac{2 \cos(x) \sin^3(x)}{3 x^2} + \frac{2}{3} \int \left(\frac{\sin^2(2x)}{x^2} - \frac{\sin^2(x)}{x^2} \right) \mathrm{d}x \end{eqnarray}$$ where the last equality used $$\begin{eqnarray} 3 \cos^2(x) \sin^2(x) - \sin^4(x) &=& 3 \cos^2(x) \sin^2(x) - \sin^2(x) (1-\cos^2(x)) \\ &=& \left(2 \sin(x) \cos(x) \right)^2 - \sin^2(x) = \sin^2(2x) - \sin^2(x) \end{eqnarray}$$ Now $$\begin{eqnarray} \int_0^\infty \frac{\sin^4(x)}{x^4} \mathrm{d}x &=& \frac{2}{3} \int_0^\infty \frac{\sin^2(2x)}{x^2} \mathrm{d} x - \frac{2}{3} \int_0^\infty \frac{\sin^2(x)}{x^2} \mathrm{d}x \\ &=& \frac{4}{3} \int_0^\infty \frac{\sin^2(y)}{y^2} \mathrm{d} y - \frac{2}{3} \int_0^\infty \frac{\sin^2(x)}{x^2} \mathrm{d}x \\ &=& \frac{2}{3} \int_0^\infty \frac{\sin^2(x)}{x^2} \mathrm{d}x = \frac{\pi}{3} \end{eqnarray}$$

-
Very nice way (+1) – user 1618033 Mar 3 '13 at 9:17

Hint: use Parseval/Plancherel theorem on $(\sin{x}/x)^2$.

That is, the FT of $(\sin{x}/x)^2$ is

$$\int_{-\infty}^{\infty} dx \: \frac{\sin^2{x}}{x^2} e^{i k x} = \begin{cases} \\\pi \left (1 - \frac{|k|}{2} \right ) & |k| \le 2 \\ 0 & |k| > 2 \end{cases}$$

Plancherel/Parseval says that

$$\int_{-\infty}^{\infty} dx \: \frac{\sin^4{x}}{x^4} = \frac{1}{2 \pi} \int_{-2 }^{2 } dk \: \pi^2 \left ( 1 - \frac{|k|}{2} \right )^2 = \frac{\pi}{2} \frac{4}{3} = \frac{2 \pi}{3}$$

$$\therefore \: \int_{0}^{\infty} dx \: \frac{\sin^4{x}}{x^4} = \frac{\pi}{3}$$

-
Thank you, that's quite an elegant way to do it. However, the problem explicitly mentions I must start from $\int_0^\infty \frac{\sin^2x}{x^2}dx$, and I'm not sure another solution will be accepted. I've changed my original post to reflect that. – Jeff Mar 1 '13 at 20:08
Well, if you or someone figures that out, it'd be a neat trick. Sadly, I have no idea how you'd do that. It's sort of akin to deriving the number $3$ from the number $4$. – Ron Gordon Mar 1 '13 at 21:15
+1 I like this method. Will be using more of it in the future. – Sasha Mar 1 '13 at 22:12

HINT: Use the relation

$$\int_0^\infty \left(\frac{\sin x}{x}\right)^n \mathrm{d}x = \frac{\pi}{2^n (n-1)!} \sum_{k=0}^{\lfloor n/2\rfloor} (-1)^k {n \choose k} (n-2k)^{n-1}$$ You may find a proof here A sine integral $\int_0^{\infty} \left(\frac{\sin x }{x }\right)^n\,\mathrm{d}x$.

-
Thank you for that solution. – Jeff Mar 1 '13 at 20:10
@Jeff: welcome! – user 1618033 Mar 1 '13 at 20:52

The following is an approach that uses contour integration.

Using the trigonometric identity $\displaystyle \sin^{4} x = \frac{1}{8} \Big(\cos 4x - 4 \cos 2x + 3 \Big)$,

\begin{align} \int_{0}^{\infty} \frac{\sin^{4} x}{x^{4}} \ dx &= \frac{1}{2} \int_{-\infty}^{\infty} \frac{\sin^{4} x}{x^4} \ dx \\ &= \frac{1}{16} \int_{-\infty}^{\infty} \text{Re} \ \frac{e^{4ix}-4e^{2ix}+3}{x^{4}} \ dx \\ &= \frac{1}{16}\int_{-\infty}^{\infty} \text{Re} \frac{e^{4ix}-4e^{2ix}+3+4ix}{x^{4}} \ dx \\ &= \frac{1}{16} \text{Re} \ \text{PV} \int_{-\infty}^{\infty} \frac{e^{4ix}-4e^{2ix}+3+4ix}{x^{4}} \ dx. \end{align}

Now let $\displaystyle f(z) = \frac{e^{4iz}-4e^{2iz}+3+4iz}{z^{4}}$ and integrate around the contour that consists of the line segment $[-R,R]$ (with a half-circle indentation of radius $r$ around the simple pole at the origin) and the upper half of the circle $|z|=R$.

Letting $r \to 0$ and $R \to \infty$ (and applying Jordan's lemma),

$$\text{PV} \int_{-\infty}^{\infty} \frac{e^{4ix}-4e^{2ix}+3+4ix}{x^{4}} \ dx- i \pi \ \text{Res}[f(z),0] = 0$$

which implies

$$\text{PV} \int_{-\infty}^{\infty} \frac{e^{4ix}-4e^{2ix}+3+4ix}{x^{4}} \ dx = i \pi \lim_{z \to 0} \frac{e^{4iz}-4e^{2iz}+3+4iz}{z^{3}} = \frac{16 \pi}{3} .$$

Therefore,

$$\int_{0}^{\infty} \frac{\sin^{4} x}{x^{4}} \ dx = \frac{\pi}{3} .$$

-

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\int_{0}^{\infty}{\sin^{4}\pars{x} \over x^{4}}\,\dd x = {\pi \over 3}:\ {\large ?}}$

$\large\tt \mbox{METHOD}\ 0:$ Let's $\ds{{\cal F}\pars{\mu} \equiv \int_{0}^{\infty}{\sin^{4}\pars{\mu x} \over x^{4}}\,\dd x}$ such that $\ds{\int_{0}^{\infty}{\sin^{4}\pars{\mu x} \over x^{4}}\,\dd x ={\cal F}\pars{1}}$. \begin{align} \color{#c00000}{{\cal F}'\pars{\mu}} &=\int_{0}^{\infty}{4\sin^{3}\pars{\mu x}\cos\pars{\mu x} \over x^{3}}\,\dd x =\int_{0}^{\infty}{\bracks{1 - \cos\pars{2\mu x}}\sin\pars{2\mu x} \over x^{3}}\,\dd x \\[3mm]&=\half\int_{0}^{\infty}{2\sin\pars{2\mu x} - \sin\pars{4\mu x} \over x^{3}}\,\dd x \quad\mbox{with}\ {\cal F}\pars{0} = 0\\[5mm]&\mbox{} \end{align} \begin{align} \color{#c00000}{{\cal F}''\pars{\mu}}&= 2\int_{0}^{\infty}{\cos\pars{2\mu x} - \cos\pars{4\mu x} \over x^{2}}\,\dd x \quad\mbox{with}\ {\cal F}'\pars{0} = 0\\[5mm]&\mbox{} \end{align} \begin{align} \color{#c00000}{{\cal F}'''\pars{\mu}}&= 2\int_{0}^{\infty}{-2\sin\pars{2\mu x} + 4\sin\pars{4\mu x} \over x}\,\dd x =4\sgn\pars{\mu}\ \overbrace{\int_{0}^{\infty}{\sin\pars{x} \over x}\,\dd x} ^{\ds{=\ {\pi \over 2}\,. \mbox{See below}}} = 2\pi\sgn\pars{\mu} \\[3mm]&\mbox{with}\ {\cal F}''\pars{0} = 0 \end{align} $$\mbox{With}\ \mu > 0\,,\ {\cal F}'''\pars{\mu} = 2\pi\ \imp\ {\cal F}''\pars{\mu} =2\pi\mu\ \imp\ {\cal F}'\pars{\mu}=\pi\mu^{2}\ \imp\ {\cal F}\pars{\mu} = {\pi \over 3}\,\mu^{3}$$ $$\color{#00f}{\large\int_{0}^{\infty}{\sin^{4}\pars{x} \over x^{4}}\,\dd x ={\cal F}\pars{1} = {\pi \over 3}\large}$$ $-----------------------------------------$
Also \begin{align} \color{#c00000}{\int_{0}^{\infty}{\sin\pars{x} \over x}\,\dd x}&= \half\int_{-\infty}^{\infty}{\sin\pars{x} \over x}\,\dd x =\half\int_{-\infty}^{\infty}\ \overbrace{\bracks{\half\int_{-1}^{1}\expo{\ic kx}\,\dd k}} ^{\ds{=\ {\sin\pars{x} \over x}}}\ \dd x \\[3mm]&={\pi \over 2}\int_{-1}^{1}\ \overbrace{\bracks{\int_{-\infty}^{\infty}\expo{\ic kx}\,{\dd x \over 2\pi}}} ^{\ds{=\ \delta\pars{k}}}\ \dd k ={\pi \over 2}\int_{-1}^{1}\delta\pars{k}\,\dd k =\color{#c00000}{\pi \over 2} \end{align} $\ds{\delta\pars{k}}$ is the Dirac Delta Function.

-
If you can justify a little bite your last integral it will be great. This one :$\int_{0}^{\infty}{\sin\pars{x} \over x}\,\dd x= \!\!\half\int_{-\infty}^{\infty}\half\int_{-1}^{1}\expo{\ic kx}\,\dd k\,\dd x$. Thanks – user119228 Apr 1 '14 at 9:49
@Julien I rewrote the last integral. I hope it will clarify the point you addressed in your comment. Thanks. – Felix Marin Apr 1 '14 at 21:52
Oh it's perfect. Very slick! (+1) – user119228 Apr 1 '14 at 22:05